Intimate Partner Violence Perpetration Among Military Spouses. Issue 15 (August 2022) - Park, Yangjin; Sullivan, Kathrine; Riviere, Lyndon A.; Merrill, Julie C.; Clarke-Walper, Kristina
Military spouses are an understudied population with respect to intimate partner violence (IPV) perpetration. Due to the unique demands of service members' jobs, military couples are documented to experience particular individual, couple, and family-level risk factors that may lead to IPV perpetration. Using the frustration-aggression hypothesis and considering the possibility of mutual violence, we examined (a) the direct effects of stressful events, marital discord, and work–family conflict on IPV perpetration among military spouses and (b) the indirect effect of anger arousal between stressful events, marital discord, and work–family conflict on IPV perpetration. This study is a secondary analysis of data drawn from a survey of army spouses conducted by the Walter Reed Army Institute of Research in 2012. The sample consists of 314 female spouses of active-duty members (white 75%, enlisted 80%). After controlling for covariates (including spouse race, rank, household size, age, living distance from military installation), the direct effects of marital discord and anger on IPV perpetration were statistically significant. Also, the direct effects of marital discord and work–family conflict on anger were significant. The path model demonstrated that the indirect effects of marital discord and work–family conflict on IPV perpetration via anger were significant. Finally, most physical and verbal violence was reported to occur in the form of mutual violence with their partners. Study findings suggest that the pathway of risk factors impacting IPV might differ depending on the sources of stress. The Family Advocacy Program, military social work practitioners, and other behavioral health providers should consider domains of risk and provide support to military spouses that is specifically tailored to these risk factors. Furthermore, considering the mediating role of anger arousal in the relationship between marital discord, work–family conflict and IPV, programs to address anger might be helpful to reduce IPV among military spouse perpetrators.